History of Entertainment Magazines within the Politics of Power and Sexuality - Formas Juitan Lase (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2020)
This article discussed the history of the entertainment magazines in Indonesia. By using the historiography method, this paper interpreted the dynamics of entertainment magazines from its birth until gradually being run over by market competition that coupled with women magazines, television, and pornography. This article also highlighted Sukarno's Political Manifesto in the practice of entertainment magazines during the Guided Democracy era. Entertainment Magazine became an instrument for the dissemination of political jargon through Kebaya. It constructed as a national identity to obstruct western ideology and culture while female sexuality that displayed feminine and sexy in kebaya were objectified through the male gaze.